PENGARUH PENERAPAN MODEL PEMBELAJARAN TIPE TIME TOKEN ARENDS TERHADAP HASIL BELAJAR PAI PESERTA DIDIK KELAS VIII DI UPTD SMPN 3 HARAU - Inti Oza; Eka Rizal; Mustafa Mustafa; Jasmienti Jasmienti (An-Nahdlah: Jurnal Pendidikan Islam, 2024)
Students' learning outcomes that have not been maximized are caused by the lack of student involvement in learning. This makes some students not understand the subject matter. This study aims to determine the effect of the application of the Time Token Arends type learning model on the PAI learning outcomes of VIII grade students at UPTD SMPN 3 Harau. This research uses a quantitative approach with a quasi-experimental design or pseudo-experiment. Data were collected through pretest and posttest. This study found a positive effect of Arends' Time Token type learning model on the PAI learning outcomes of VIII grade students at UPTD SMPN 3 Harau. The hypothesis test results show that the sig. (2-tailed) pretest and posttest of the experimental class and control class 0.000≤ 0.05, it can be concluded that the use of the Time Token Arends type learning model affects the learning outcomes of VIII grade students at UPTD SMPN 3 Harau.